The plumber's troubleshooting guide - Woodson, R. Dodge (New York : McGraw Hill Education, 1994)
Plumbing Troubleshooting Techniques That Save Time and Money. Say goodbye to time-consuming trial and error methods, extra work, and unnecessary fixture replacements. In The Plumber's Troubleshooting Guide Master Plumber R. Dodge Woodson show you how to develop finely-tuned troubleshooting skills for all types of residential and commercial plumbing fixtures and systems. In a clear, easy-to-understand style, he advises you on how to go beyond normal causes to uncover often overlooked reasons for problems and malfunctions in: toilets and urinals; sinks; bathtubs; faucets and valves; spas and whirlpools; water distribution systems; draining and vent systems; specialty fixtures; well and water treatment systems; septic systems; waste-water pumps; appliances.
Ch. 1. Understanding the Art of Troubleshooting -- Ch. 2. How Effective Troubleshooting Saves Time and Money -- Ch. 3. Troubleshooting Toilets -- Ch. 4. Troubleshooting Sinks and Lavatories -- Ch. 5. Troubleshooting Bathtubs -- Ch. 6. Troubleshooting Showers -- Ch. 7. Troubleshooting Spas and Whirlpools -- Ch. 8. Troubleshooting Bidets -- Ch. 9. Troubleshooting Urinals -- Ch. 10. Troubleshooting Faucets and Valves -- Ch. 11. Troubleshooting Plumbing Appliances -- Ch. 12. Troubleshooting Waste-Water Pumps -- Ch. 13. Troubleshooting Specialty Fixtures -- Ch. 14. Troubleshooting Well Systems -- Ch. 15. Troubleshooting Septic Systems -- Ch. 16. Troubleshooting Water Treatment Systems -- Ch. 17. Troubleshooting Water Distribution Systems -- Ch. 18. Troubleshooting Drainage and Vent Systems.
Includes index.
Keywords: PLUMBING